Dilute magnetic semiconductor (DMS) materials for spintronics - Kok, Hui Jun. (2009)
Nickel and Cobalt- doped Zinc Oxide nanowire arrays were fabricated using the electrochemical deposition method by varying the potentials, dopant concentrations and concentration ratios between zinc and the doping element. The nanowire arrays were found to possess different orientation order and density level which may be due to variation in deposited contents and compositions. Magnetic properties of the nanowire arrays were also analyzed. The nucleation and growth process of the nanowires reflects strong dependencies on the potential and the concentration of the solution used in the fabrication. In addition, room temperature ferromagnetism was also found in the nanowires arrays. Characterization of nanowires was done using scanning electron microscope (SEM), X-ray photoemission spectroscope (XPS), X-ray energy dispersive spectroscopy (EDS) and Vibrating Sample Magnetometer (VSM). It was shown that an appropriate potential is needed for the growth of hexagonal crystal shaped nanowires due to the high free energy barrier of activation hindering its nucleation on bare silicon wafer. The growth of nanowires was found to be closely related with the concentration of dopant due to the available amount of hydroxide ions needed for the anisotropic growth of Zinc Oxide nanowires. The presence of methenamine in the solution was also proven to be essential for the growth of nanowires by acting as a pH buffer and slowly supplying hydroxide ions.